Public relations - Kokab, Adila; Murslin, Ammara (Oakville, Ontario, Canada Society Publishing, 2018)
The main purpose of this book is to introduce you with the concept of public relations. This book is based on the introduction of public relations and what’s it importance. Whether this book is being used for discovering new fields or it is a part of educational program or course, this book will help you with your cause. Therefore, this book is written in very straightforward writing style.
Chapter 1 "Definition and Core Concept of Public Relations", this chapter examines the definition of public relations, the psychology of Public Relations communications, its type like sound communication, symbols communication, and some other way of communication which are important for building up the Public Relations. This chapter also describes the reason that why public relation is going to be more vital now a days. The chapter also inspects the origin of public relation. It also examines the characteristics of ideal public relations man.

Chapter 2 "History of Public Relations and its Stages", this chapter examines the development of public relations through different periods of time. It also gives a brief description of people who played important role in the development of public relations. This chapter describes the history period from Dark Age to twentieth century and public relations firms throughout the history. It also describes PR publications and PR job opportunities throughout the history.

Chapter 3 "Processes of Public Relations", this chapter examines the different stages of public relations process. This will help us in building good public relations through different processes. These processes include STARE, RACE, GRACE, ACE, PACE, and ROSIE.

Chapter 4 "Functions of Public Relations", this chapter examines the functions, public relations play in community relations, employee relations, media relations and product publicity etc. how public relations functions to improve these relations. Functions tell us about how public relations build and maintain these good relations. It also tells us about how public relations monitor the attitude of people.

Chapter 5 "Models of Public Relations", this chapter describes the four models of public relations named as press agentry/publicity model, public information model, two way asymmetrical model and symmetrical model. It gives brief description of these four models.

Chapter 6 "Public Relations as a Management Function", this chapter describes role of public relations in management, how it help in crisis management and the role of public relations in business sharpness.

Chapter 7 "Management of Public Relations", this chapter describes how we can manage good public relations among public. What are those characteristics that help in building a trustworthy relationships.

Chapter 8 "Difference between Public Relations and other terms", this chapter examines the key point on which basis public relation can be distinguished from other terms like advertising, marketing and journalism as people take these terms as synonymic.

Chapter 9 "Effective Skills for Public Relations", this chapter examines the skills that are necessary for building good face among publics, associations and companies. This chapter includes Writing as well as other skills for making your relations with public stronger.

Chapter 10 "Benefits of Public Relations", this chapter describes the importance of public relations why public relations knowledge is vital today How PR helps us in our daily life as well as in our jobs. It also describes some of the advantages PR provides us with.
Includes bibliographical references and index
Keywords: Public relations